Analisis Sistem Pemerintahan Berbasis Koalisi Partai Politik Berkaitan dengan Sistem Presidensial Menurut Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Aida, Nurul; Isharyanto, , (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2022)
This study aims to analyze the coalition in the administration of the presidential system according to the 1945 Constitution of the Republic of Indonesia and its influence on executive and legislative relations. The purpose of this article is to determine the existence of coalitions based on the constitution and their influence. The findings prove that based on the results of the research conducted, it shows that the 1945 Constitution of the Republic of Indonesia only regulates the coalition at the beginning of the presidential election and does not regulate how the coalition will take place afterwards, as well as the position of the coalition in the administration of government. The relationship that arises between the legislative executive can be seen from the legislative function and the supervisory function. In the climate of a fat coalition built by the president, in fact, it does not produce effective relations between the president and the DPR in terms of the quantity and quality of legislation. The implementation of the right of interpellation, the right of inquiry, and the right to express an opinion also cannot be carried out effectively and ideally, such conditions will interfere with the creation of checks and balances between the president and the DPR.